Enhancing surface production of negative ions using nitrogen doped diamond in a deuterium plasma. (20th August 2020) - Smith, Gregory J; Ellis, James; Moussaoui, Roba; Pardanaud, Cédric; Martin, Céline; Achard, Jocelyn; Issaoui, Riadh; Gans, Timo; Dedrick, James P; Cartry, Gilles
Abstract: The production of negative ions is of significant interest for applications including mass spectrometry, particle acceleration, material surface processing, and neutral beam injection for magnetic confinement fusion. Methods to improve the efficiency of the surface production of negative ions, without the use of low work function metals, are of interest for mitigating the complex engineering challenges these materials introduce. In this study we investigate the production of negative ions by doping diamond with nitrogen. Negatively biased (−20 V or −130 V), nitrogen doped micro-crystalline diamond films are introduced to a low pressure deuterium plasma (helicon source operated in capacitive mode, 2 Pa, 26 W) and negative ion energy distribution functions are measured via mass spectrometry with respect to the surface temperature (30 °C to 750 °C) and dopant concentration. The results suggest that nitrogen doping has little influence on the yield when the sample is biased at −130 V, but when a relatively small bias voltage of −20 V is applied the yield is increased by a factor of 2 above that of un-doped diamond when its temperature reaches 550 °C. The doping of diamond with nitrogen is a new method for controlling the surface production of negative ions, which continues to be of significant interest for a wide variety of practical applications.